When Myths Incarnate Performances: The 12th Krisnayana Performances as Cultural Discourse and Emotional Experience - Syaiful Qadar Basri; Setyo Yanuartuti; Anbie Haldini Muhammad; Kanzul Fikri (Universitas Negeri Medan, 2026)
This research aims to examine the representation of the myth of Krishna in the performance of the 12th Kresnayana based on the play Suta Ruhara, focusing on the relationship between dramatic structure, the emotional experience of the audience and the performer, and the aesthetic transformation of performance in the contemporary social context. The research uses a qualitative approach with a case study method, including script analysis, direct observation of performances, audiovisual documentation, and in-depth interviews with actors and audiences. The analysis is carried out through an interpretive phenomenological perspective to understand affective experience as part of the production of performance meaning. The results of the study show that myths are not positioned as static epic narratives, but rather as ethical discourses that are alive and negotiated through the tragedies of Samba, Boma, Hagnyanawati, with Krishna appearing as a figure of moral wisdom and a balancer of conflicts. The novelty of this research lies in the finding that affection in performance does not function solely as a dramatic effect, but as a space for collective ethical reflection that connects myths, bodily experiences, and the social consciousness of the audience. Aesthetic transformation through the fusion of traditional idioms and contemporary performance technologies reinforces the symbolic articulation of myths without eliminating local roots. This study concludes that the 12th Kresnayana acts as a reflective cultural practice that bridges traditions, emotional experiences, and social realities, and offers a model of traditional performing arts development that is adaptive, pedagogical, and relevant to the dynamics of today's society.